Analysis of genetic divergence in basil (Ocimum spp.) - Anjali Shrivastava, Prabha Nirmodh, Mayuri admin Sahu, A K Geda, (Journal of Spices and Aromatic Crops, 2008)
Analysis of 21 basil (Ocimum spp.) genotypes grown at Raipur (Chhattisgarh) revealed thata maximum of five genotypes were accommodated in clusters I and II followed by fourgenotypes in clusters III and V, and three genotypes in cluster IV. The intra-cluster distancebetween members of cluster IV was maximum followed by clusters I, II, III and V, suggestingthat the genotypes in cluster IV were relatively more diverse.